Real estate exposure of US banking industry stock returns: evidence from commercial and residential markets - Lee, Ming-Te; Kuo, Shew-Huei; Lee, Ming-Long (International Journal of Strategic Property Management, 2018)
This study is the first to address the exposure of banking industry stock returns to both the commercial and residential real estate markets. The empirical findings show that U.S. banking industry stock returns are significantly sensitive to real estate market returns after controlling for stock market, interest rate, and exchange rate effects. Moreover, the commercial and residential real estate markets have very different effects on banking industry stock returns. Furthermore, the effects on banking industry stock returns are state-dependent. The findings have valuable implications for investors, managers and regulatory authorities.